Photodegradation and adsorption processes in treatment of methyl orange dye and palm oil mill effluent by titanium dioxide-impregnated chitosan systems - Ab Hamid, Siti Nor (2018)
In this work, palm oil mill effluent (POME) was treated by using photodegradation and adsorption processes with the presence of titanium dioxide and chitosan catalyst. The titanium dioxide was combined chitosan (TiO2-CS) through impregnation at varying conditions. At certain instances Methyl Orange (MO) dye, which served as a model pollutant was used as adsorbate. Parameters such as initial concentrations (20 to 100 ppm), pH (pH 3 to pH 9), contact time and TiO2-CS loadings (0.10-1.00 g), and different catalytic systems were investigated. The optimum ratio of TiO2-CS loadings used in this study was 2:1 (TiO2:CS). Meanwhile, the optimum amount of TiO2 and CS was 0.20 g and 0.10 g respectively at pH 4.5 for one hour of reaction with the total removal percentage of 20.0% and the colour removal of 70.0% POME by using TiO2- CS. This prove that high colour removal is not an indicator for high COD removal. The TiO2-CS catalyst could not be reused for further investigation after one hour of reaction, due to the instability of the materials. The problem was overcome by coating titanium dioxide and chitosan onto glass beads (TiO2-CS/GB). The performance of the coated catalyst has been investigated in Methyl Orange (MO) removal. It was found that 20.00 g of glass beads was required for the optimum coating of titanium dioxide and chitosan. The maximum loading of TiO2 and chitosan on the glass beads was approximately 1.0 g. The immobilised catalyst was tested for MO removal at concentration in range of 20 to 100 ppm. Photodegradation and adsorption of MO using TiO2-CS/GB with the presence of light and in the dark have been proved to obey the first order kinetic model. The optimum pH of the solution with the highest removal percentage was 3.0, and the removal percentage increased with the increasing temperature. Besides, the coated catalyst was able to be reused for up to six cycles using 20 ppm of MO. The percentage COD removal for POME by using TiO2-CS/GB was 40.0%, which was twice as much compared to unsupported TiO2-CS and the colour removal achieved 100.0%.